Intercultural Conflict and Experiences of International Students in Turkey - Ahmed Abdulatif Hajjismael; Hamed Osman Alfahim Osman; Gocheva Svetla (De Gruyter, 2020)
Conflict is a part of daily life and it can occur for many reasons. In an intercultural environment, both international and local people can face conflict due to their interactions. Even though there has been an exponential increase in the growth of international students in Turkey in recent years, little is known about their experiences in the realm of intercultural conflicts. Therefore, the main objective of this study was to assess the occurrence of intercultural conflicts among international students at Anadolu University. In particular, the study sought to examine possible intercultural conflicts this group of students might experience, international students' intercultural awareness, the major sources of the intercultural conflict and how the international students cope with intercultural conflict. A qualitative research method with phenomenological research design was utilized and semi-structured in-depth interviews were used to gather data. The analysis of the study was organized into six themes, namely: awareness, approach, experience, communication style, worldview change, and coping strategy. Except for the last theme, the obtained data aligned with the literature. Findings revealed that the international students experienced intercultural conflicts mainly due to lack of intercultural competence. Based on these findings, recommendations for future studies were suggested.